Percepção docente do programa Educar pra Valer (EpV) na rede pública de ensino no município de Mamanguape na Paraíba - Lima, Maria de Lourdes Pereira de (2024)
The Educar pra Valer (Educate for Value) program was set up by the Bem Comum Association (ABC) to support Brazilian municipalities in implementing management practices. It is based on evidence and results from the experience of the municipality of Sobral and the PAIC program in Ceará, with the Lemann Foundation as its supporter. Implemented in the public school system in the municipality of Mamanguape/PB in Early Years Elementary School in 2019, it consists of diagnosing, evaluating and improving performance rates, especially in reading for students who had learning deficits in this category for whatever reason. In this sense, the general objective of this research is to analyze the possible contributions of the Educar pra Valer program as an educational policy aimed at literacy at the right age and the formation of fluent readers, verified in the 5th grade classes of the municipal schools of Mamanguape/PB, in 2022, according to the teachers' perceptions. On the axis of education in contemporary times, a dialog was promoted with the authors Pereira (2006), Jakimiu (2021), and with legal documents CF (1988), LDBEN (1996), PNE (2014), BNCC (2018), etc.; on the axis of public policies, Oliveira (2011), Höfling (2001), Sousa and Silva (2016), etc. were taken up. in the area of the EpV program, we used websites and documents on ABC (2018), EpV (2018, 2022; 2023), Lemann Foundation (2019), Lyceum Consultoria Ltda. (2018), Cooperation Agreement (2019), Work Plan (2019), etc.; in the area of teachers' perceptions, we used Ball and collaborators (2021), Freitas (2012; 2014), etc., to provide analysis and discussion. To achieve this objective, we opted for descriptive research according to Machado (2023), with a quantitative-qualitative approach, according to Minayo (2001; 2002). To generate the data, a questionnaire was applied, based on Prodanov and Freitas (2013) and documentary analysis, according to Guba and Lincoln (1981). The locus of this research was the municipality of Mamanguape/PB, with ten teachers participating who worked with the EpV program in 5th grade classes in 2022. The results obtained after analyzing the data show that the objectives of the EpV program were partly achieved, given that 50% of the teachers reported that the students who received the techniques and methodologies applied by this program in 2019 entered the 5th grade classes in 2022 with satisfactory reading skills, and that 60% of these same teachers stated that, based on their work with the EpV program in 2022, the majority of these students had the knowledge to be fluent readers. However, in order to achieve its objectives, the EpV program has narrowed its curriculum and changed its methodology, causing teachers to lose their autonomy in choosing teaching materials and to use structured material instead. In addition to being constantly charged and supervised in their school routine, in the schedule of activities, they are evaluated according to the results obtained in the evaluations, mainly in the summative and large-scale ones, which promote ranking among schools, and can also cause discomfort for some teachers if they fail to achieve the expected success in these evaluations.